Dundun talking drum - Tiamiyu, Sidikat Ebun; Kayode, Ibisankale D.; Kadibis Entertainment (Australia : Kadibis Entertainment Productions, 2007)
Dundun (The Talking Drum) takes the viewer to the city of Oyo in Nigeria where the drum is believed to have originated. This comprehensive documentary shows the cultural and historical context surrounding the drum and an in-depth examination of its construction, from chopping down the correct tree to the finishing design touches
History of the drum -- custordian's of dundun drum -- the kings drummer -- uses of drum -- making of the drum -- the gods of the drum
Title from title screen
Executive producer, Ademola Adeoshun, Olumide Madariola, Ibisankale D. Kayode
Narrator: Dotun Taylor
DVD format
Keywords: Rites and ceremonies -- Africa; Africa -- Social life and customs; Africa -- Religious life and customs